Measurements of Euglena motion parameters by laser light scattering. - Ascoli, C (1978)
Measurements of Euglena gracilis motion parameters have been performed by the spectral analysis of the scattered laser light. Samples were oriented by a radiofrequency field to obtain easily interpretable spectra. Cell rotation frequency and flagellar beating frequency distributions were obtained from the homodyne spectra, whereas the Doppler lines obtained at small observation angles by heterodyne detection yielded the swimming speed distributions. We discuss the broadening of the heterodyne spectra at large angles of observation. An application of this method to the study of the photo-kinetic effect is also described.